Thioxanthone–carbazole as a visible light photoinitiator for free radical polymerization - Yilmaz, Gorkem; Tuzun, Alev; Yagci, Yusuf (Wiley, 2010)
AbstractA thioxanthone (TX) derivative with the additional carbazole chromophore, namely thioxanthone‐carbazole (TX‐C) was synthesized and characterized. The photophysical properties and its efficiency to polymerize methyl methacrylate both in the presence and absence of N,N‐dimethylaniline (DMA) as coinitiator was investigated and compared with that of the commercially available TX. TX‐C was found to display better photophysical properties and in both cases initiate polymerization more efficiently. Detailed real‐time Fourier transform infrared studies revealed that high polymerization rates can be obtained when TX‐C in conjunction with DMA was used. © 2010 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem, 2010